Konsep Bagi Hasil Dalam Perspektif Islam - Kartiko, Ari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2019)
Profit sharing was well known by mudharabah in Islamic worldview or cooperation done by two person and more were agreed on various sides. It's done between creditor and bussinessman or expertman. The main modal on this concept not only money and wealth but also honesty and social feels are more important. Helping each other and enjoying success and being responsible for the difficulties with working together to find solutions is part of the goal of the concept of mudaraba offered by Islam. With the concept of Muslims, especially business people can run their business with financial support from borrowers without having to be burdened with interest that binds and becomes a burden at the time of profit and loss, so that the economic wheel can be implemented in accordance with Islamic teachings and away from interest.